Monitoring of the curing process in precast concrete slabs: An experimental study. (30th September 2016) - Ranz, J.; Aparicio, S.; Fuente, J.V.; Anaya, J.J.; Hernández, M.G.
Highlights: A real time quality control methodology of the curing process for precast concrete is presented. A wireless sensor network was developed to measure temperature and ultrasonic velocity. Three different models were used to estimate the compressive strength. The proposed methodology was tested in three precast concrete plants in Spain. Abstract: In this paper a methodology for the quality control of the curing process in precast concrete plants is presented by non-destructive testing techniques. This methodology consists on a remote monitoring system and a method to estimate the strength gain of the precast elements during the curing process. The remote monitoring system is based on Wireless Sensor Networks (WSN) provided with temperature, humidity and ultrasonic sensors. The compressive strength is estimated using two different procedures, one based on temperature and the other one on ultrasonic velocity measurements. Comparing the compressive strength estimations obtained using temperature and ultrasonic velocity measurements, the concrete quality during early ages of curing can be controlled, and arising problems can immediately be detected. This methodology was tested in three different precast concrete plants in Spain.